2013
DOI: 10.3390/toxins5101723
|View full text |Cite
|
Sign up to set email alerts
|

Small Chemical Chromatin Effectors Alter Secondary Metabolite Production in Aspergillus clavatus

Abstract: The filamentous fungus Aspergillus clavatus is known to produce a variety of secondary metabolites (SM) such as patulin, pseurotin A, and cytochalasin E. In fungi, the production of most SM is strongly influenced by environmental factors and nutrients. Furthermore, it has been shown that the regulation of SM gene clusters is largely based on modulation of a chromatin structure. Communication between fungi and bacteria also triggers chromatin-based induction of silent SM gene clusters. Consequently, chemical ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 82 publications
2
38
0
2
Order By: Relevance
“…Recently, the ability of small molecule effectors, like valproic acid (VPA), to inhibit the catalytic activity of HDACs and to modulate the subsequent “cryptic” expression profile of secondary metabolites has been shown in fungi ( Shwab et al, 2007 ; Cole, 2008 ; Cichewicz, 2010 ; Hagemann et al, 2011 ). Furthermore our previous study suggests that the effect of VPA seems to be target specific in fungi ( Zutz et al, 2013 ).…”
Section: Introductionmentioning
confidence: 91%
“…Recently, the ability of small molecule effectors, like valproic acid (VPA), to inhibit the catalytic activity of HDACs and to modulate the subsequent “cryptic” expression profile of secondary metabolites has been shown in fungi ( Shwab et al, 2007 ; Cole, 2008 ; Cichewicz, 2010 ; Hagemann et al, 2011 ). Furthermore our previous study suggests that the effect of VPA seems to be target specific in fungi ( Zutz et al, 2013 ).…”
Section: Introductionmentioning
confidence: 91%
“…16 Like prior reports 12,17-20 we have used broad-spectrum chemical HDAC inhibitors; however, we have also reduced levels of a single HDAC, RpdA (AN4493) 7,21 and quantified the changes in expression of secondary metabolomes (Figure 1). Upon rpdA knockdown, we found that 61 compounds have >100 fold increases in their relative levels and 47 have >100 fold decreases.…”
Section: Introductionmentioning
confidence: 99%
“…Since it was not isolated from maize, human risks appear to be reduced. Earlier studies have reported this species to produce a variety of secondary metabolites (SM) such as patulin, pseurotin A and cytochalasin E (Zutz et al, 2013). On the other hand, other species which did not produce toxin in this study have been reported to be toxigenic in earlier studies for example; A. candidus was reported to produce a mycotoxin known as AcT1 (Chattopadhyay et al, 1987), whereas A. awamori has been reported to produce fumonisins (Storari et al, 2012) and aspochalamins A-D (Gebhardt et al, 2004).…”
Section: Discussionmentioning
confidence: 54%